Konsep Pendidikan Integral Dalam Surat Al-Alaq Ayat 1-5: (Kajian Filosofis Terhadap Tafsir Al-Azhar Karya HAMKA) - A. Syafi' AS. (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2020)
This study aims to describe and analyze the concept of integral education in Hamka's Tafsir Al-Azhar, a tafsir book written by Hamka when he was in prison. This research is a literature research (library research) using a philosophical approach, which is to carry out focused, deep and fundamental thoughts and reflections on Hamka's interpretation of the verses of the Koran relating to the object of research by paying attention to the laws of thought. Meanwhile, the data analysis method uses content analysis method, which is a method of analysis based on the content (meaning) of a text. The results of this study indicate that Hamka's interpretation of surah al-‘Alaq verses 1-5 contains the concept of integral education, that in education there is a unity of the science system as a process of dialectical relations between the body and the spirit and the human environment in understanding the verses of Allah, as well as in demanding. science must always rely on Allah SWT. In addition, according to Hamka, integral education is education that is aimed at realizing true human beings (students).